Recombinant human granulocyte macrophage colony stimulating factor (hGM-CSF): Possibility of nanoparticle-mediated delivery in cancer immunotherapy. Issue 2 (4th March 2017) - Vanitha, Selvarajan; Chaubey, Nidhi; Ghosh, Siddhartha S.; Sanpui, Pallab
ABSTRACT: Most of the cancer treatment strategies from chemotherapy to radiotherapy render cancer cells apoptotic and these apoptotic cancer cells accumulate at the tumor sites. The accumulation of apoptotic cancer cells often result in inflammation and autoimmune responses causing serious health implications. Macrophages, which are effective immune combatants, can help in the clearance of these deleterious occupants. Granulocyte macrophage colony stimulating factor (GM-CSF) is a key cytokine, modulator of immune system and responsible for growth and differentiation of granulocytes and macrophages. In this regard, supply of recombinant GM-CSF can enhance the capability of macrophages for clearance of apoptotic cancer cells. However, delivery of the cytokine in vivo can suffer from certain disadvantages like faster depletion, less stability and low targeting efficiency. We believe that the stability and sustained release of GM-CSF can be improved through its encapsulation inside appropriately designed nanoparticles.